The language of school design design patterns for 21st century schools - Nair, Prakash; Fielding, Randall; Lackney, Jeffery A. (DesignShare, 2009)
Includes best practice case studies culled from some of the most widely recognized school facilities the world over. Authors Prakash Nair and Randall Fielding have dipped into a vast treasure trove of award-winning, innovative school designs from 20 countries to illustrate their cutting-edge concepts. --from publisher description